2013
DOI: 10.1007/s12031-013-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Determinants for a Potent Mammalian TRPA1 Antagonist by Utilizing Species Differences

Abstract: The transient receptor potential A1 (TRPA1) receptor is a member of the TRP family and an excitatory nonselective cation channel. An increasing body of evidence suggests that TRPA1 acts as a nociceptor for various chemicals and physical stimuli. Thus, many TRPA1 antagonists have been developed as analgesic agents. Recently, we found that AP18, a mammalian TRPA1 antagonist, does not inhibit heterologously expressed western clawed frog TRPA1 (fTRPA1). Here, we show that fTRPA1 is also insensitive to A967079, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…It has been shown that two amino acid residues located in the predicted inner site of TM5 are critical for the antagonistic action of AP18 (26). Similarly, we recently reported that these two amino acid residues (serine 873 and tyrosine 874) on human TRPA1 were also important for the antagonistic effect of A967079 (29). Furthermore, by analyses using a homology model of TRPA1 based on Kv1.2, it has also been reported that phenylalanine 944, valine 948, and isoleucine 950 in the predicted loop between TM5 and TM6 are involved in the antagonistic action of A967079 (38).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been shown that two amino acid residues located in the predicted inner site of TM5 are critical for the antagonistic action of AP18 (26). Similarly, we recently reported that these two amino acid residues (serine 873 and tyrosine 874) on human TRPA1 were also important for the antagonistic effect of A967079 (29). Furthermore, by analyses using a homology model of TRPA1 based on Kv1.2, it has also been reported that phenylalanine 944, valine 948, and isoleucine 950 in the predicted loop between TM5 and TM6 are involved in the antagonistic action of A967079 (38).…”
Section: Discussionsupporting
confidence: 53%
“…By utilizing species differences, we identified two amino acid residues located within the putative fifth transmembrane (TM5) domain as critical determinants for the antagonistic action of A967079 (29). Quite recently, we also analyzed functional properties of chicken TRPA1, and we reported that it is a heat sensor, but not a cold one, unlike rodent TRPA1 (30).…”
Section: Trpa1mentioning
confidence: 99%
“…S2d,e). CA concentrations higher than the reported EC 50 values (0.13 mM and 0.39 mM for hTRPA1 and fTRPA1, respectively) were chosen1013, and we waited for the CA-evoked currents to be stabilized or desensitized. Figure 1a and b shows the reversible current responses of wild type hTRPA1 (wt-hTRPA1) and fTRPA1 (wt-fTRPA1) to repeated application of 0.3 and 0.5 mM CA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For example, A967079 (A96) and AP18, both of which are structurally similar, are potent mammalian TRPA1 antagonists, although their inhibitory effects on TRPA1 vary among species101112. Comparative and mutagenesis experiments with TRPA1 from different species revealed that several amino acids in the TM5 domain are crucial to the effects of these two antagonists91213. Furthermore, a recent study reporting the detailed structure of human TRPA1 identified a binding site for A96 that is in the vicinity of sites found previously14.…”
mentioning
confidence: 99%
“…Electrophilic compounds are known to activate TRPA1 through covalent modification of cysteines and a lysine in the N-terminal region (12,13). In addition, the S5/S6 domain may serve as a target region for nonelectrophilic agonists, including menthol (14), eudesmol (15), and protons (16), or several antagonists (17,18), including the potent inhibitor A-967079 (14,(19)(20)(21). Furthermore, a recent electron cryo-microscopy (cryo-EM) study (22) has revealed the high-resolution structure of TRPA1 bound to an agonist or antagonists.…”
mentioning
confidence: 99%